Assessment of Metabolic Parameters in Female Triathletes with Hashimoto’s Thyroiditis in Poland - Marcin Gierach; Roman Junik (Biomedicines, 2023)
Background: Hypothyroidism is a complex disorder characterized by an increase in body weight. About 15–30% of hypothyroid patients are reported to be overweight. The triathlon is an endurance combination sport that comprises a sequential swim, cycle, and run. Triathletes must withstand high training loads with various combinations of intensity and volume. Adequate body structure, the ratio of fat and muscle tissue, and adequate hydration play a huge role. The aim of our study was to show the potential differences in metabolic parameters assessed by medical Body Composition Analyzer before the initiation of treatment with L-thyroxine and after 3 and 6 months of treatment in females who practiced triathlon and who were newly diagnosed with Hashimoto’s thyroiditis. Methods: The study group included 32 females practicing triathlon. They were recruited for 10 months from March to December 2021. Analysis of anthropometric measurements was performed using a seca device mBCA 515 medical Body Composition Analyzer. Results: We observed significant differences in FM and VAT before and after L-thyroxine treatment. We also noticed lower BMI levels after treatment, along with significant differences in thyroid function tests (TSH and fT4) carried out during the recruitment period and after 3 and 6 months of treatment. Conclusion: Due to their higher daily energy consumption, further research is needed into the treatment of Hashimoto’s thyroiditis in athletes who practice triathlon. Frequent bioelectrical impedance analysis of body composition during treatment can be very helpful.